Assessing positive body image, body satisfaction, weight bias, and appearance comparison in emerging adults: A cross-validation study across eight countries. (December 2020) - Aimé, Annie; Fuller-Tyszkiewicz, Matthew; Dion, Jacinthe; Markey, Charlotte H.; Strodl, Esben; McCabe, Marita; Mellor, David; Granero Gallegos, Antonio; Pietrabissa, Giada; Alcaraz-Ibánez, Manuel; Bégin, Catherine; Blackburn, Marie-Ève; et al.
Highlights: This paper examines four measures related to positive body image across eight countries. The measurement invariance of the BAS-2, BASS, PACS, and WBIS-M was examined. In general, findings suggest the utility of these measures across countries. Measures were more likely to vary as a function of differences in BMI and gender. Abstract: Positive body image refers to individuals' ability to conceptualize their bodies with love, respect, and appreciation. The study of positive body image is relatively new, and instruments used to investigate this multi-faceted construct have received limited use in non-English speaking countries. Thus, the aim of this investigation is to consider four measures that are associated with positive body image across eight different countries. Participants ( n = 6272) completed the Body Appreciation Scale-2, the Body Areas Satisfaction Scale, the Physical Appearance Comparison Scale, and the Weight Bias Internalization Scale. Multi-group confirmatory factor analyses (MG-CFAs) and item-response theory (IRT) models were used to examine the measurement invariance of these surveys. Our results generally suggest that positive body image, weight bias, and appearance comparison can be assessed using brief assessments and that these four instruments can be used in different countries, but care should be taken to consider individuals' gender, BMI, and socio-economic position.